Pathologic examination of placenta: a study on 500 live births to assess conformity to College of American Pathologists (CAP) guidelines and clinicopathologic correlation. (18th October 2022) - Mubeen, Aysha; Makary, Raafat
Abstract: Purpose: Pathological examination of placenta is vital to understand the pathophysiology of adverse perinatal outcomes, prevention of recurring conditions in subsequent pregnancies and medico-legal risk assessment. The College of American Pathologists (CAP) has published a set of guidelines to help guide the submission of placentas to pathology. However, awareness and conformity to these guidelines are not well established and vary from one institution to the other. We aimed to examine the appropriateness of placental pathologic examination at our institution and their conformity to guidelines in this audit type study to help improve our practices. Materials and methods: Detailed retrospective review of obstetrical records was performed including history and delivery reports for a total of 500 consecutive live births noting whether the placenta was sent for pathologic evaluation according to CAP guidelines. Sensitivity and specificity of placental examination were calculated based on the 2 × 2 contingency table. Results: The sensitivity and specificity of pathologic examination of placenta in conformity to CAP guidelines were 63.4% and 91.6%, respectively. The most common indications for submission were maternal followed by fetal and placental indications. Concordant clinico-pathologic correlation was found in 87/135 placentas submitted. Conclusions: Placenta has long been ignored with limited understanding of the value of its examination. More awareness of CAP guidelines is needed to appropriately submit placentas for pathologic examination. Each institution needs to develop their own set of guidelines taking guidance from CAP guidelines and tailored to its population. Meaningful communication between obstetricians, neonatologists, and pathologists is key to improving the utility of pathologic examination of placenta and the application of results for better patient care.